The Kyoto Protocol without USA and Australia - with the Russian Federation as a strategic permit seller - Bjart Holtsmark (Statistics Norway, Research Department, 2003)
After the U.S. and Australian withdrawal from the Kyoto Protocol, and the extension of national quotas in the Bonn- and Marrakesh-agreements, meager environmental effects and a low price of emission permits is likely to be the outcome of implementation. This paper provides an analysis of these prospects for the Kyoto Protocol and the international permit market based on different assumptions related to the baseline scenario. Possible strategic behavior in the permit market is emphasized: A contribution of the paper is to take into consideration potential conflicting Russian interests in the market for natural gas in Europe and the market for emission permits under the Kyoto Protocol. The Russian Federation is a large supplier with the potential for exercising market power in both these markets. The analysis shows that the Russian interests in the gas market may lead Russia to increase export of emission allowances and consequently contribute to a low permit price. The applied analytical tool is a partial equilibrium model of the market for emission allowances and the fossil fuel markets.
Keywords: Q30; Q41; 330; Emissions trading; Permit price; Fossil fuel markets; Natural gas market; Kyoto Protocol; Market power.